NANING PRANOTO IN THE SOUL OF INDONESIA’S LITERATURE - Woro Januarti (Prosiding Seminar Nasional Sasindo, 2020)
In modern Indonesian literature, it can be said that female writers are still less prestigious than male writers. The problems raised in literature touch a lot with the relationship between men and women, patriarchal culture, and colonialism, accompanied by women's object as a male commodity. Call it a writer in the New Pujangga era like Selasih, then in the independence era Ida Nasutin, Walujati, St. Nuraini, Suwarsih Djojopuspito, to S. Rukiandi. Also N.H. Dini, Hanna Rambe, until in the 2000s, women writers such as Dee Lestari, Ayu Utami, Djenar Maesa Ayu, and others emerged. This research focuses on examining the literary works of Naning Pranoto, who are post-reform and pre-reform writers. The writer Naning Pranoto has produced twenty novels and more than a hundred short stories. Also, to this day, Naning Pranoto is still active in "Creative Writing," which has made the world of Indonesian literature healthy: preparing for new writers' birth. If, during the colonial era, the house of Tjokroaminoto was the sprouting area for the nation's leader's birth, the term "Mbok Naning's hut" was the home for the birth of new literary shoots. So this research is considered very important to explore the soul of Naning Pranoto in the world of Indonesian literature. This research uses a qualitative descriptive method, collects Naning Pranoto's literary works and journals that discuss Naning Pranoto's work then provides a red line of its constituent elements from feminism, politics, ecology, colonialism, culture, and religion. Therefore, studying Naning Pranoto's literary works is equivalent to adding more attention to important figures' gold ink in Indonesian literature's history in the future and her phenomenal works